(untitled) (Journal of Hama University, 2020)
The objective of this study was to compare the effect of using intravaginal sponges with intramuscular (IM) injection of prostaglandin hormone within the reproductive season and their effect on Lambing rate and birth rate in Awassi ewes. Thirty ewes were equally divided into two groups (G1 and G2). Intravaginal sponges impregnated with 60 mg of Medroxy Progesterone Acetate (MAP) were inserted into the ewes of the first group for 14 days, and were injected at the time of the withdrawal of sponges with 500 IU of equine Chorionic Gonadotrophin (eCG) at the first group ewes (G1). The ewes in second group (G2) were injected with double dose of 125 μg of prostaglandin (PGF2α) intramuscularly (IM) at 9 days apart. The ewes were naturally mated with fertile rams (ram / 5 ewes). The results showed that there were significant differences between groups (G1 and G2) in the Lambing rate (93.33% vs. 73.33%). and the ewes of group (G1) outperformed the ewes of group (G2) in the percentage of twin births (42.86% vs. 18.18%), and the birth rate (1.43 vs. 1.18) with significant difference (P<0.05). We conclude from the study that treating ewes by using intravaginal sponges with eCG injection was better than the method of prostaglandin injection in raising the Lambing rate and birth rate in Syrian Awassi ewes, within the local Syrian conditions.